PENGARUH KEHALUSAN SEMEN TERHADAP KUAT TEKAN MORTAR - Afni, Nur; Sahara, Sahara; Hernawati, Hernawati (Universitas Islam Negeri Alauddin Makassar, 2015)
This study aims to determine the effect of fineness to compressive strength of cement mortar. Mechanical parameters measured are fineness and compressive strength. From these test results, lead to the conclusion that the overall mechanical properties of the cement and mortar for all treatments meet the Indonesian National Standard (SNI) in 2004, the highest level of refinement that is 410.8 kg/m2, while the lowest is 387 kg/m2. For the compressive strength at age 3 days produces the highest value is 181 kg/m2, while the lowest is 143 kg/m2, at the age of 7 days resulted in the highest value is 242 kg/m2, while the lowest is 204 kg/m2, at the age of 28 days produces the highest value is 350 kg/m2, while the lowest is 265 kg/m2. Concluding that the more finely granular cement eat the higher the compress strength.